2014
DOI: 10.1016/j.jacc.2014.02.545
|View full text |Cite
|
Sign up to set email alerts
|

Current Treatment of In-Stent Restenosis

Abstract: Management of patients with in-stent restenosis (ISR) remains an important clinical problem. Although drug-eluting stents (DES) have drastically reduced the incidence of ISR, treatment of DES-ISR is particularly challenging. ISR mainly results from aggressive neointimal proliferation, but recent data also suggest that neoatherosclerosis may play an important pathophysiological role. Intracoronary imaging provides unique insights to unravel the underlying substrate of ISR and may be used to guide repeated inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
350
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(367 citation statements)
references
References 97 publications
5
350
0
2
Order By: Relevance
“…Coronary angiogram revealed a mid-proximal LAD stenosis (Fig. 1J) adjacent to the proximal LAD BRS (scaffold restenosis, according to the current definition within 5 mm proximal and distal to the stent/scaffold [5]). The lesion was treated with a sirolimus drug-eluting stent.…”
mentioning
confidence: 94%
“…Coronary angiogram revealed a mid-proximal LAD stenosis (Fig. 1J) adjacent to the proximal LAD BRS (scaffold restenosis, according to the current definition within 5 mm proximal and distal to the stent/scaffold [5]). The lesion was treated with a sirolimus drug-eluting stent.…”
mentioning
confidence: 94%
“…Additionally, an extreme inflammatory response was detected post MI, and the improvement of inflammation had an important role in ventricular remodeling and promotion of left ventricular ejection fraction (LVEF) (5). In addition, In-Stent Restenosis (ISR) is one of the important complications after PCI, which depends on CV risk factors (6,7), such as inflammation (8), hyperlipidemia (9), and lesion features (10). A prior study indicated that Copyright ISR was common in patients undergoing PCI (6,11).…”
Section: Introductionmentioning
confidence: 99%
“…Drug eluting stent in‐stent restenosis (DES‐ISR) is a known limitation in clinical practice following percutaneous coronary intervention 1. Despite its inherent biological and technical limitations, the use of a second DES (“stent sandwich”) is a common therapeutic approach among practicing physicians 2.…”
Section: Introductionmentioning
confidence: 99%